Effectiveness of Giving Orange and Tomato Juice to Optimize Potato Growth and Production - Jamilah Nasution; Riyanto; Riris Meriati Sitorus; Emmy Harso Kardhinata; Edi Azwar (Jurnal Penelitian Pendidikan IPA, 2025)
Fruit waste management has gained increasing attention as an eco-friendly approach to sustainable agriculture. The increasing accumulation of organic waste, particularly from fruit residues, poses a significant environmental challenge. Utilizing these waste materials for agricultural purposes can contribute to waste reduction and soil fertility improvement. This study aimed to evaluate the effects of orange and tomato juice application on the growth and yield of potato plants (Solanum tuberosum L.), considering the potential of fruit waste as an organic fertilizer. A Randomized Block Design (RBD) was employed with two treatments: orange juice and tomato juice, each at five concentration levels (0%, 25%, 50%, 75%, and 100%) with three replications, totaling 75 samples. The parameters observed included the number of leaves, stem height, number of tubers, and tuber weight. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The results indicated that orange juice significantly increased leaf number, stem height, and tuber weight, while tomato juice had a limited effect. No significant interaction was observed between the two treatments. These findings highlight the potential of fruit waste as an alternative organic fertilizer for sustainable agriculture.